Understanding Science Concepts In The Basic Natural Sciences Course Through The Inquiry Method - Sitti Nurfaidah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the implementation of the inquiry method in the Basic Natural Sciences course and analyze its impact on students' understanding of science concepts. The study employed a descriptive qualitative approach with a case study design. The participants consisted of a lecturer and students enrolled in the Basic Natural Sciences course. Data were collected through classroom observations, in-depth interviews, and learning documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation, member checking, and peer debriefing. The findings revealed that the inquiry method was implemented through several stages, namely problem identification, question formulation, hypothesis development, data collection, data analysis, and conclusion drawing. The implementation of the inquiry method encouraged active student participation in scientific investigations and classroom discussions. Students demonstrated a deeper understanding of science concepts by connecting theoretical knowledge with real-life phenomena. In addition, the inquiry method enhanced students' critical thinking skills, problem-solving abilities, and scientific literacy. Although several challenges were identified, including differences in students' academic backgrounds and the availability of learning resources, the inquiry method proved effective in promoting meaningful and contextual learning experiences. In conclusion, the inquiry method is an effective learning strategy for improving students' conceptual understanding of science in the Basic Natural Sciences course. Therefore, it is recommended as a student-centered instructional approach that supports the development of 21st-century competencies.